Entamoeba histolytica - Pathogenic Protozoan of the Large Intestine in Humans - Piotr Nowak; Katarzyna Mastalska; Jakub Loster (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2015)
Entamoeba histolytica is a cosmopolitan, parasitic protozoan of human large intestine, which is a causative agent of amoebiasis. Amoebiasis manifests with persistent diarrhea containing mucus or blood, accompanied by abdominal pain, flatulence, nausea and fever. In some cases amoebas may travel through the bloodstream from the intestine to the liver or to other organs, causing multiple abscesses. Amoebiasis is a dangerous, parasitic disease and after malaria the second cause of deaths related to parasitic infections worldwide. The highest rate of infections is observed among people living in or traveling through the tropics. Laboratory diagnosis of amoebiasis is quite difficult, comprising of microscopy and methods of molecular biology. Pathogenic species Entamoeba histolytica has to be differentiated from other nonpathogenic amoebas of the intestine, so called commensals, that very often live in the human large intestine and remain harmless. Other intestinal commensals are Entamoeba dispar and Entamoeba moshkovskii, morphologically the same as pathogenic species Entamoeba histolytica sensu stricto. The differential diagnosis of these three amoebas is possible with detection of their DNA